KOLONISASI BAKTERI METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS (MRSA) PADA UANG KERTAS YANG BEREDAR DI KANTIN FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Chandra, Katherine Silvania; Mayura, I Putu Bayu; Budayanti, Ni Nyoman Sri; Budayanti, Ni Nyoman Sri; Hendrayana, Made Agus (E-Jurnal Medika Udayana, 2024)
Money serves as a widely utilized medium of transactional value in society. The risk of infection resulting from bacterial dissemination on paper currency is notably high. Infections caused by microorganisms on paper currency are largely caused by bacteria that resist antibiotics, exemplified by Methicillin-Resistant Staphylococcus aureus (MRSA). The resistance exhibited by these bacteria to antibiotic treatments has claimed millions of lives and can lead to substantial global health repercussions. Therefore, this study aims to ascertain the presence of Methicillin-Resistant Staphylococcus aureus (MRSA) bacteria contaminating paper currency. This research was conducted with observational methodology and a descriptive cross-sectional approach. Thirty samples of paper currency are swabbed, and specimens are subsequently inoculated onto Staphylococcus medium. Colonies of Staphylococcus are re-identified using gram staining, catalase tests, followed by coagulase tests to ascertain the presence of Staphylococcus aureus bacteria. Isolates are classified as Methicillin-Resistant Staphylococcus aureus (MRSA) if the inhibition zone measures less than or equal to 21 mm. The research findings indicate the colonization of Staphylococcus aureus and Methicillin-Resistant Staphylococcus aureus (MRSA) bacteria on the paper currency circulating in the canteen of the Medical Faculty at Udayana University. The percentage of Staphylococcus aureus colonization is 56.66% and Methicillin-Resistant Staphylococcus aureus (MRSA) colonization is 53.33%. Keywords : Paper Currency, Methicillin-Resistant Staphylococcus aureus(MRSA).